Electrospun Fibrous Tapes: Heat‐Shrinkable Electrospun Fibrous Tape for Restoring Structure and Function of Loose Soft Tissue (Adv. Funct. Mater. 8/2021). (17th February 2021) - Saiding, Qimanguli; Jin, Jing; Qin, Menglu; Cai, Zhengwei; Lu, Min; Wang, Fei; Cui, Wenguo; Chen, Xinliang
Abstract : In article number 2007440, Wenguo Cui, Xinliang Chen, and co‐workers fabricate a heat‐shrinkable electrospun fibrous tape whose contraction causes relaxed fascia to pull back at body temperature. The retractive force is transformed into mechanical stimulation, which promotes the nuclear transfer co‐transcriptional factor YAP, and eventually allowing for new extracellular matrix deposition. The heat‐shrinkable fibrous tape is highly promising for the repair of loose soft tissue both structurally and functionally.